"Splitting the matrix": intussusceptive angiogenesis meets MT1‐MMP. Issue 2 (20th December 2019) - D'Amico, Gabriela; Muñoz‐Félix, José M; Pedrosa, Ana Rita; Hodivala‐Dilke, Kairbaan M
Abstract : Pathological angiogenesis contributes to tumour progression as well as to chronic inflammatory diseases. In this issue of EMBO Molecular Medicine, Esteban and co‐workers identify endothelial cell MT1‐MMP as a key regulator of intussusceptive angiogenesis (IA) in inflammatory colitis. Thrombospondin 1 (TSP1) cleavage by MT1‐MMP results in the binding of the c‐terminal fragment of TSP1 to αvβ3 integrin, which induces nitric oxide (NO) production, vasodilation and further initiation of IA. This novel control mechanism of inflammatory IA points towards promising new therapeutic targets for inflammatory bowel disease. Abstract : Prof. Hodivala‐Dilke and colleagues discuss the findings from Esteban et al (in this issue of EMBO Molecular Medicine) that targeting intussusceptive angiogenesis via the TSP1‐nitric oxide axis exhibits therapeutic efficacy in the context of inflammatory bowel disease.